2014
DOI: 10.7547/0003-0538-104.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Does Foot Placement Affect the Reliability of Static Foot Posture Measurements?

Abstract: Based on these findings, we recommend that clinicians perform measurements of static foot posture using the same standing foot placement between sessions to ensure a high level of measurement consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…This was selected as a functional position for the foot, whilst reducing the influence of balance that would be required for a single leg stance positions. To improve repeatability across sessions and testers [22], foot position was standardised using a template that aligned the medial borders of each foot parallel and 20 cm apart (to enable access of the ultrasound probe). With the foot flat on the floor, ultrasound imaging was possible from the dorsal and medial aspects of the foot.…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…This was selected as a functional position for the foot, whilst reducing the influence of balance that would be required for a single leg stance positions. To improve repeatability across sessions and testers [22], foot position was standardised using a template that aligned the medial borders of each foot parallel and 20 cm apart (to enable access of the ultrasound probe). With the foot flat on the floor, ultrasound imaging was possible from the dorsal and medial aspects of the foot.…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…Entre estas herramientas se encuentra la plataforma de medición antropométrica del pie (p-MAP), que ha sido utilizada previamente y descrita a nivel internacional pero no en lengua española, con el nombre de Foot Assessment Platform (FAP). Además, las herramientas de medición deberían seguir un protocolo claro de utilización para que los resultados sean comparables, ya que un cambio en la posición del sujeto puede modificar los resultados obtenidos y, por lo tanto, inducir a error 18 .…”
Section: Introductionunclassified
“…Already in 1967 Hlavac demonstrated that positioning of the foot in neutral, supinated, and pronated position alters the osseous relationships within the foot on radiographs [11,19]. Since then, other studies supported the importance of the posture and positioning of the foot [20][21][22]. X-rays are therefore often taken at the base of gait (midstance phase of gait) [2,11,12], in which the weight is about equally divided over both feet.…”
Section: Introductionmentioning
confidence: 99%